(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
The 127 species of lichenized and 5 species of lichenicolous fungi are recorded. Lecanora atrosulphurea (Wahlenb.) Ach. is new for the lichen biota of Ukraine and 55 species are new for «Kam`yani Mogyly» as branch of the Ukrainian Steppe Reserve. 14 previously reported lichen species were excluded from the list as misidentified. The total list of species include information about synonyms, substrates and herbaria, where they are deposited.